Lebanon : Report on Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2005)
This Report assesses the Observance of Standards and Codes on Fiscal Transparency for Lebanon. There appears to be insufficient public understanding of, or interest in, the critical need for sustained fiscal reforms. The government's program of reform needs to be based on more analysis, including a clearly articulated vision of what the strengths and problems are. The successful implementation of medium-term objectives requires a revamping of the way the government plans, executes, and assumes responsibility for its actions, hence of all elements of budget preparation and execution.